ANALYSIS OF PROBLEM SOLVING ABILITY IN MATHEMATICS BASED ON CONCEPT UNDERSTANDING AND MATHEMATICS REASONING ABILITY OF CLASS VIII STUDENTS AT SMPN 29 MAKASSAR - Salahuddin Salahuddin (Universitas Negeri Makassar, 2018)
The study aims at examining (1) The presence or not of the influence concept understanding and Mathematics reasoning ability of Problem Solving Ability in Mathematics based either individually or together with students of class VIII SMPN 29 Makassar, and (2) problem solving ability in Mathematics based on concept understanding and Mathematics reasoning ability. The study is descriptive research is a mix-methode with quantitave-qualitative approach. The researcher acted as the instrument who has guided by test of Mathematics concept understanding and valid interview guidance. Data were collected through test provision and verified by interview. The subjects of the study were three students in class VIII at SMPN 29 Makassar consisted of on students of PKPMT, on students of PKPMS, and one students of PKPMR. The results of the study reveal that (1) there is influence concept understanding of Problem Solving Ability in Mathematics based equal to 36,50% through estimate function = 15,659 + 0,751X1. There is influence Mathematics reasoning ability of Problem Solving Ability in Mathematics based equal to 40,05% through estimate function 14Å¶